Probing the proteome to explore potential correlates of increased Alzheimer's‐related cerebrovascular disease in adults with Down syndrome. Issue 10 (24th February 2022) - Moni, Fahmida; Petersen, Melissa E.; Zhang, Fan; Lao, Patrick J.; Zimmerman, Molly E.; Gu, Yian; Gutierrez, José; Rizvi, Batool; Laing, Krystal K.; Igwe, Kay C.; Sathishkumar, Mithra; Keator, David; et al.
Abstract: Cerebrovascular disease is associated with symptoms and pathogenesis of Alzheimer's disease (AD) among adults with Down syndrome (DS). The cause of increased dementia‐related cerebrovascular disease in DS is unknown. We explored whether protein markers of neuroinflammation are associated with markers of cerebrovascular disease among adults with DS. Participants from the Alzheimer's disease in Down syndrome (ADDS) study with magnetic resonance imaging (MRI) scans and blood biomarker data were included. Support vector machine (SVM) analyses examined the relationship of blood‐based proteomic biomarkers with MRI‐defined cerebrovascular disease among participants characterized as having cognitive decline (n = 36, mean age ± SD = 53 ± 6.2) and as being cognitively stable (n = 78, mean age = 49 ± 6.4). Inflammatory and AD markers were associated with cerebrovascular disease, particularly among symptomatic individuals. The pattern suggested relatively greater inflammatory involvement among cognitively stable individuals and greater AD involvement among those with cognitively decline. The findings help to generate hypotheses that both inflammatory and AD markers are implicated in cerebrovascular disease among those with DS and point to potential mechanistic pathways for further examination.